IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PERUMAHAN BERSUBSIDI DENGAN METODE TOPSIS BERBASIS WEB DI KABUPATEN MOJOKERTO - Ananda Wildan Fadhlulloh; Mashuri, Chamdan; Lazulfa, Indana; Kristianto, Hery (Inovate, 2024)
A house is an essential element in meeting the needs of life as a shelter for every resident. KabupatenMojokerto is a region with the potential for population growth, thus increasing the demand for housing.Currently, there are many housing developments in Kabupaten Mojokerto with various criteria, making itdifficult for prospective buyers to decide on a house that meets their needs. To address this issue, theresearcher provides a solution to help determine the right choice of subsidized housing using a DecisionSupport System (DSS). A DSS is a tool used to assist in the decision-making process by analyzing data,applying criteria, and providing appropriate alternative recommendations. In implementing this DSS, theresearcher uses the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method forthe decision-making process. This research aims to design and implement an effective DSS and apply theTOPSIS method in the decision-making process. The result of this research is a web-based application. Theresearch findings show that the system can provide accurate recommendations in line with userpreferences. The developed DSS is expected to assist local governments and property developers inunderstanding and meeting the community's needs for subsidized housing, thereby enhancing theeffectiveness of the subsidized housing program in Mojokerto Regency.Keywords: DSS, TOPSIS, Housing, Mojokerto.